The Influence of Reward, Punishment, and Work Environment on Work Discipline of Employees of Pt Tunas Dwipa Matra Kepahiang Branch - Widia Permata Sari; Eti Arini (Penerbit Jurnal Indonesia, 2023)
This study entitled The Effect of Reward, Punishment, and Work Environment on Work Discipline of Employees of PT Tunas Dwipa Matra, Kepahiang Branch. The formulation of the problem in this study is whether the effect of reward, punishment, work environment on employee work discipline at PT Tunas Dwipa Matra Kepahiang branch. The purpose of this study was to determine whether the effect of reward, punishment, and work environment on the work discipline of employees of PT Tunas Dwipa Matra, Kepahiang branch. By using research test data analysis techniques, the results of the data can be concluded that the respondents' perceptions of Rewards (X1), Punishment (X2), Work Environment (X3) and Discipline (Y) with multiple linear regression results obtained the following equation: Y = 5.148 + 0.206 (X1) + 0.425 (X2) + 0.433 (X3) indicates that there is a positive effect between Reward (X1) Punishment (X2) and Work Environment (X3) on Work Discipline (Y). Variables Reward (X1), Punishment (X2) led to the determination of the effect of Discipline (Y) of R2 = 0.603 or approximately (60.3%) through individual (partial) and joint (simultaneous) hypothesis testing in this study using the t and f test, Reward (X1), Punishment (X2) and Work Environment (X3) = 0.000, meaning that the fsign value < 0.05 indicates that together they have a significant effect.